Islamic Moral Education Values in the Selection Poems on the Life of Prophet Muhammad by Paul Abdul Wadud Sutherland and Its Implication on Students’ Literature Learning - Mutiarani Mutiarani; Khaerunnisa Khaerunnisa; Zaitun Zaitun; Clara Clarisa (English Language in Focus (ELIF), 2023)
This research contains literary learning in the poetry genre entitled Poems on the Life of the Prophet Muhammad by Paul Abdul Wadud Sutherland. This poem has the moral education value of Al-Islam and Kemuhammadiahan which is the main focus of this research because moral values is one of the basic foundations of human nature which is closely related to human behavior with God. This research aims to obtain a deep understanding of moral values in the form of divine values and human values from the collection of poems Poems on the Life of the Prophet Muhammad by Paul Abdul Wadud Sutherland. This research uses a qualitative method and content analysis design. The research finding showed that Shutherland’s Poems on the Life of the Prophet Muhammad contained the Islamic moral education values namely illahiyah values and insaniyah values that can be good examples for students’ daily life.